PENGARUH TAX AUDIT, SANKSI PAJAK DAN MODERNISASI SISTEM ADMINISTRASI PERPAJAKAN TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Jamil, Siti Nur Aisi Isnen; Ratnasari, Fina (Publika Citra Media, 2025)
This study was conducted with the aim of knowing and proving the Influence of Tax Audit, Tax Sanctions, and Modernization of Tax Administration System on Individual Taxpayer Compliance. This study is a type of quantitative research, using primary data in the form of distributing questionnaires. The sampling method in this study was convenience sampling, namely a sampling method where researchers choose individuals or groups that are easily accessible or widely available to be part of the sample. This study used a population of individual taxpayers at KPP Pratama Jakarta Cilandak by taking a sample of 100 respondents, then the data was processed using IBM SPSS Statistics 26. The results of the study showed that simultaneously tax audits, tax sanctions, and modernization of the tax administration system were able to jointly influence individual taxpayer compliance. While partially tax audits did not affect individual taxpayer compliance, tax sanctions affected individual taxpayer compliance, and modernization of the tax administration system affected individual taxpayer compliance.